Continuous Literacy Program For All (CLP FALL) to Strengthen Muslim Students' Literacy Culture at Primary School - Isgandi, Yiyin (JELTII (Journal of English Language Teaching and Islamic Integration), 2018)
The phenomenon of Primary School children is more fun to play games than reading and writing books. The literacy capability assessment of students in Indonesia by International Association of Educational (IAE) and Organization for Economic Co-operation and Development (OECD) from 2011-2015 still below the everage score as well as the country ranking. In 2015 the Ministry of Education and Culture socializes the massive School Literacy Movement named Gerakan Literasi Sekolah (GLS). However in fact, the majority of Primary Schools in Indonesia is less sensitive and cannot implement the program well in school. In order to solve the problem, the principal and teachers in the Primary School needs to apply the Continous Literacy Program for All (CLP FALL) consistently and measurably. By using Watson-Guthrie’s behaviorism theory and Piaget’s cognitive theory this program should be applied and developed. The program includes three pahases; 1) planning, 2) implementation, and 3) evaluation and development. The gradual implementation includes daily, weekly, monthly, semester, and annual activities involving all academic members.